Sudden stops in Latin America and the Caribbean during COVID-19 - Eduardo A. Cavallo; María José González; Juan Hernández; Andrew Powell (Inter-American Development Bank (IDB), 2022)
External capital accounts suffered during the COVID-19 crisis in Latin America and the Caribbean, but perhaps surprisingly the impacts were less severe than in previous crises. Gross capital inflows offset the outflows of residents, in sharp contrast to the global financial crisis of 2008/09 when residents' repatriation of capital countered withdrawals from non-residents. In general, the result was relatively stable net capital inflows and modest current account adjustments. Still, some countries that had seen inflows fall prior to the crisis, reflecting weaker fundamentals, suffered Sudden Stops in net capital flows. Given accommodating global monetary policy, sound fundamentals ensured access to liquid international capital markets, reducing the impacts of Sudden Stops during the pandemic.
Keywords: F30; F32; F40; 330; Sudden stops; Gross and net capital flows; External accounts; COVID19; Latin America and the Caribbean